Synergistic effect of glucose and prolactin on GLUT2 expression in cultured neonatal rat islets - Crepaldi-Alves, S. C. [UNESP]; Carneiro, E. M. [UNESP]; Bosqueiro, José Roberto [UNESP]; Boschero, A. C. (FapUNIFESP (SciELO), 1997)
We studied the synergistic effect of glucose and prolactin (PRL) on insulin secretion and GLUT2 expression in cultured neonatal rat islets. After 7 days in culture, basal insulin secretion (2.8 mM glucose) was similar in control and PRL-treated islets (1.84 ± 0.06% and 2.08 ± 0.07% of the islet insulin content, respectively). At 5.6 and 22 mM glucose, insulin secretion was significantly higher in PRL-treated than in control islets, achieving 1.38 ± 0.15% and 3.09 ± 0.21 % of the islet insulin content in control and 2.43 ± 0.16% and 4.31 ± 0.24% of the islet insulin content in PRL-treated islets, respectively. The expression of the glucose transporter GLUT2 in B-cell membranes was dose-dependently increased by exposure of the islet to increasing glucose concentrations. This effect was potentiated in islets cultured for 7 days in the presence of 2 μg/ml PRL. At 5.6 and 10 mM glucose, the increase in GLUT2 expression in PRL-treated islets was 75% and 150% higher than that registered in the respective control. The data presented here indicate that insulin secretion, induced by different concentrations of glucose, correlates well with the expression of the B-cell-specific glucose transporter GLUT2 in pancreatic islets.
Keywords: Glucose; Glucose transporter; Pancreatic islets; Prolactin; glucose; glucose transporter; glucose transporter 2; prolactin; animal; biosynthesis; culture technique; metabolism; pancreas islet; physiology; rat; Animals; Cell Culture Techniques; Glucose Transporter Type 2; Islets of Langerhans; Monosaccharide Transport Proteins; Rats